2020
DOI: 10.1108/ijcst-04-2020-0051
|View full text |Cite
|
Sign up to set email alerts
|

A review of the current status of microfiber pollution research in textiles

Abstract: PurposeMicrofiber is one of the major sources of microplastic emission into the environment. In recent times, research on microfiber has gained momentum, and research across different disciplines was performed. However, no complete study was performed from the viewpoint of textiles to analyse the microfiber shedding behaviour by relating the properties textiles. The purpose of this paper is to analyse the microfiber shedding behaviour in textiles.Design/methodology/approachArticles on the microfiber shedding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 33 publications
(61 reference statements)
0
22
0
Order By: Relevance
“…Since then, a number of other reviews on the topic have appeared [2]- [11] that complement reviews that had been there previously [12] [13] [14] [15] [16]. Nevertheless, the authors felt the need to extend the scope of the earlier review as it focused too much on plastic microbeads, an area of our research [17] at the time of writing, and too little on other forms of microplastics such as microtires [18] [19] and textile fibers [20] [21]. In addition, the contribution of the different sources of microplastics as found in the wastewater is changing over time, especially with the gradual phase-out of microplastic content in rinse-off cosmetics [22] [23] [24] and the ban in certain regions of plastic bags [25] and single use plastics [26], both potential materials for microplastics due to subsequent degradative fragmentation processes.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a number of other reviews on the topic have appeared [2]- [11] that complement reviews that had been there previously [12] [13] [14] [15] [16]. Nevertheless, the authors felt the need to extend the scope of the earlier review as it focused too much on plastic microbeads, an area of our research [17] at the time of writing, and too little on other forms of microplastics such as microtires [18] [19] and textile fibers [20] [21]. In addition, the contribution of the different sources of microplastics as found in the wastewater is changing over time, especially with the gradual phase-out of microplastic content in rinse-off cosmetics [22] [23] [24] and the ban in certain regions of plastic bags [25] and single use plastics [26], both potential materials for microplastics due to subsequent degradative fragmentation processes.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, many studies have provided estimates of microfiber emissions from synthetic textiles during machine washing. Numerous studies and results show that textiles are among the main potential polluters due to the release of fibres, and that one of the reasons for this is the washing process [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Research has shown that the type of construction itself affects the amount of microfibers released.…”
Section: Textiles—source Of Microplastic Pollutionmentioning
confidence: 99%
“…Knitted fabrics were also found to release more fibres. Other researchers suggest that the selection of a suitable spinning method could control the structural compactness and thus solve the problem of loose structures, hairiness, and twisting of the yarn [ 43 , 80 ]. De Falco et al have found that fabrics release more microfibres than knitwear, depending on the type of fibres used in the textile production.…”
Section: Textiles—source Of Microplastic Pollutionmentioning
confidence: 99%
“…While microfiber pollution needs to be addressed through the entire textile chain from fibers to consumers, technology innovation in the textile industry will mitigate the problem at the source. The developments of new types of fiber production, the innovation of design, and production processing of yarn and fabric are important methods to reduce microfiber release because of the shedding of yarn hairiness and fluff on clothes at the source, although very few research data are found on the effect of yarn and fabric properties on the microfiber release (Rathinamoorthy and Raja Balasaraswathi 2020). The development and Fig.…”
Section: Control Microfiber Pollution At the Sourcementioning
confidence: 99%